Counseling: Application in the Muslim community setting - Abdullah, Seif Abdullah (2005)
Muslims have concrete life guidance that manifest itself in the Quran and the prophetic traditions, however, they are not completely immune from the psychological imbalances in their lives. Like any other people in this world they face many types of difficulties in their lives that create havoc and maladjustment's in their personalities. These maladjustment's pose as catalysts to anxieties and stubborn thresholds to an individual’s and group’s normal functioning. In Islamic thinking and belief, Muslims admit that the human is made up of two different creations, the spirit and the body. Al Ghazali, one of the great and famous Muslim scholars asserts "happiness and misery are caused by the conditions of the soul". The soul is a substance by itself (al Ghazali) but the body of a human being relies on the soul to achieve its optimum functioning. The human soul is not perfect in nature and when it joins the human body, it is subject to some influences of human desires that pollute its status and fall sick with some mischievous diseases. Among the diseases of the soul that have direct implications to hunan functioning are sorrow, excessive anger, unrealistic fear, selfishness, destructive envy, dissatisfaction, rancor, and failure to stick to Allah’s guidance. Therefore, this paper is an attempt to provide some useful interventions that could be used to properly deal with these human predicaments in the Muslim communities in order to achieve the real happiness in our lives in this world and that of hereafter. Some essential counseling interventions in the Muslim communities include strengthening their souls, strengthen their Iman, awareness of whom they are (self-awareness), the purpose of their creation, analyzing things and occasions rationally, eradication of negative thinking and self defeating thoughts, patience and prayers, understanding that life calamities are part of our lives as tests, fighting the narcissistic self talk, etc.